2023
DOI: 10.3390/jrfm16090406
|View full text |Cite
|
Sign up to set email alerts
|

Credit Risk Determinants in Selected Ethiopian Commercial Banks: A Panel Data Analysis

Seid Muhammed,
Goshu Desalegn,
Maria Fekete-Farkas
et al.

Abstract: The study aims to investigate the factors that contribute to credit risk in Ethiopian commercial banks, considering both macroeconomic and bank-specific factors. The research utilized multiple regression models, a quantitative research approach, and explanatory research designs. A purposive sample technique was used to select 10 commercial banks for the study, and secondary data from audited financial reports were analyzed. The findings of the study reveal a significant positive relationship between credit ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The extensive range of operations and products offered by large banks may result in a loss of control, thereby increasing the level of risk. Consistent with this view, Swami et al [ 51 ], and Muhammed et al [ 3 ] pointed out that bank’s size is positively linked with risks.…”
Section: Literature Review and The Hypotheses Developmentmentioning
confidence: 83%
See 2 more Smart Citations
“…The extensive range of operations and products offered by large banks may result in a loss of control, thereby increasing the level of risk. Consistent with this view, Swami et al [ 51 ], and Muhammed et al [ 3 ] pointed out that bank’s size is positively linked with risks.…”
Section: Literature Review and The Hypotheses Developmentmentioning
confidence: 83%
“…Thus, we expect low credit risk during high economic growth. However, Antony and Suresh [ 46 ] pointed out that GDP is positively associated with credit risk while Kharabsheh [ 54 ] and Muhammed et al [ 3 ] found that GDP has no significant impact on credit risk.…”
Section: Literature Review and The Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve this objective, quantitative research approaches and an explanatory research design were used utilizing a random-effect regression model conducted through Stata 14 software. According to (Muhammed et al (2023), Ethiopia is home to 29 commercial banks, with 27 being predominantly privately owned. Hence, given the lion's share of private banks in the nation's financial sector, and the recommendations of previous studies by Teshome et al (2018), Tekatel (2019), and Xu et al (2021) that highlighted the significant impact of capital structure choices on the financial performance of privately owned banks, this study exclusively focused on private banks.…”
Section: Methodsmentioning
confidence: 99%
“…Developing nations' banking businesses are particularly vulnerable to capital structure decisions because of their low equity-to-total asset ratios and stringent regulations (Sivalingam and Kengatharan 2018). Ethiopia's banking industry is crucial for the nation's economy, contributing more than 4.2% to the GDP and representing over 95% of the capital (Muhammed et al 2023;Tekatel 2019;Abate and Kaur 2023). Any disruption or failure in this sector would greatly impact the country's overall economic development.…”
Section: Introductionmentioning
confidence: 99%